Three-year clinical performance of monolithic and partially veneered zirconia ceramic fixed partial dentures - Habibi, Yasamin; Dawid, Marie-Theres; Waldecker, Moritz; Rammelsberg, Peter; Bömicke, Wolfgang (Journal of esthetic and restorative dentistry, 2020)
Objective To compare the 3-year survival and success rates of monolithic (M) and partially veneered (PV) zirconia-fixed partial dentures (FPDs). Materials and Methods Sixty-seven FPDs (n = 33 M-FPDs; n = 34 PV-FPDs) were placed in 51 patients (n = 23 males; mean age 61.5 years) and clinically followed up 1 week, 6 months, and then yearly after placement. One hundred per cent (100%) of M-FPDs and 70% of PV-FPDs were located in the posterior region. Ninety-two per cent (92%) of M-FPDs had three units, whereas 50% of PV-FPDs had more than three units. A facial veneer was present in 73% of the PV-FPDs units. Survival and success were calculated using the Kaplan-Meier method and compared using the log-rank test (α = .05). Results The mean observation period was 3.5 years for M-FPDs and 3.1 years for PV-FPDs. Most complications associated with FPDs were biological in nature. Ceramic defects occurred exclusively among PV-FPDs. Three-year survival was 96.7% for M-FPDs and 93.8% for PV-FPDs (P = .064). Three-year success was 93.8% for M-FPDs and 81.7% for PV-FPDs (P = .039). Conclusions The use of both M-FPDs and PV-FPDs yielded clinically successful results over a mean period of 3 years. Clinical Significance By using monolithic or facially veneered zirconia, ceramic FPDs could be fabricated which showed only a minimum of technical complications over the period of investigation without sacrificing adequate esthetics.
First published: 30 January 2020
Gesehen am 26.11.2021
This research was orally presented at the 68th Annual Scientific Meeting of the German Society of Prosthetic Dentistry and Biomaterials, Rostock, Germany